The Development and Comparative Evaluation of Rosemary Hydroalcoholic Macerate-Based Dermatocosmetic Preparations: A Study on Antioxidant, Antimicrobial, and Anti-Inflammatory Properties - Alaa Sahlabgi; Dumitru Lupuliasa; Gabriela Stanciu; Simona Lupșor; Lavinia Lia Vlaia; Ramona Rotariu; Nicoleta Corina Predescu; Cristiana Rădulescu; Radu-Lucian Olteanu; Sorina-Geanina Stănescu; Lucian Hîncu; Magdalena Mititelu (Gels)
This study investigates the development and comparative evaluation of new dermatocosmetic preparations based on hydroalcoholic macerates of rosemary (Rosmarinus officinalis L.), focusing on their antioxidant, antimicrobial, and anti-inflammatory properties. For this purpose, rosemary hydroalcoholic macerations were analyzed by evaluating the content of biologically active compounds, determining their antioxidant and antimicrobial capacity. Total polyphenol content (TPC), determined via the Folin–Ciocâlteu method, reached 2155 ± 2.45 mg GAE/100 g fresh weight in the 70% ethanol macerate (RDS2) of rosemary from Dobrogea, significantly exceeding (p < 0.05) the values observed in the Bulgarian samples. The highest antioxidant activity (745 ± 2.33 mg GAE/100 g fresh weight) correlated with this extraction. Atomic absorption spectroscopy (AAS) analysis revealed elevated calcium (119.5 mg/kg), zinc, and iron levels in Dobrogean rosemary compared to its Bulgarian counterparts. Antimicrobial assessments demonstrated that the 70% ethanol macerate (RDS2) of Dobrogean rosemary exhibited the strongest inhibitory effects, particularly against Staphylococcus aureus (inhibition zone: 11–23 mm), while its activity against Escherichia coli was moderate (10–17 mm at 30 µL). Candida albicans was also significantly inhibited, with an inhibition zone of 9–20 mm. In contrast, the Bulgarian rosemary macerate (RBS2) exhibited weak inhibition against the tested microorganisms. The higher antimicrobial activity of the RDS2 is likely due to its enriched polyphenolic content, including carnosic acid and rosmarinic acid, which are known for their bioactive properties. These findings highlight Dobrogean rosemary’s superior bioactive properties, supporting its use in formulations with antioxidant and antimicrobial benefits.